A Method to Develop Landfill Liner Material Using Design of Experiments Methodology - SHAHZAD, MAHEEN (İstanbul Kültür Üniversitesi, 2023)
This thesis presents a method for developing landfill liner materials using the Design of Experiments (DoE) methodology. The study focuses on identifying key DoE methods used in construction material development, specifically for landfill liners. The study evaluates the effectiveness of DoE methods in optimizing liner properties and assesses the potential benefits of using DoE in this context. Although limited research exists introducing the use of DoE in construction material development, to the best of our knowledge, a study discussing the application of DoE methods for developing landfill liners has not been published yet. This study analyzes previous studies to determine if DoE methods have the potential to improve liner performance in terms of strength and hydraulic conductivity. It synthesizes findings to evaluate broader implications, such as cost savings, increased efficiency, and improved environmental outcomes. The thesis applies the first four stages of the DoE methodology by identifying factors affecting liner properties, defining response variables, and designing the experiments. Results include a design matrix based on a central composite design (CCD) matrix. Overall, the study recommends using DoE methodology for developing landfill liner materials, providing a systematic approach for future research. This research contributes to understanding DoE methods in optimizing construction materials and offers potential for improved landfill system performance.
Deney Tasarımı Metodolojisi Kullanılarak Atık Sıfır Astar Malzemesi Geliştirme Yöntemi
▪ Yüksek lisans tezi.
Keywords: Liner Material; Design of Experiment Methodology; CCD design; Optimization